INFLUENCE OF NICKEL ON THE MICROSTRUCTURE AND MECHANICAL PROPERTIES OF ALUMINUM COPPER ALLOY - Vu Anh Tuan (Journal of Mechanical Engineering Research and Developments, 2019)
This paper presents the results of Nickel component on the microstructure and mechanical properties of the aluminum-copper alloy. With the same heat treatment process (heated to 850oC quenching in water and tempering at 350oC in 2h) noticed: the sample was added nickel, it had phases of nickel with Al and Fe; these phases make sample’s mechanical properties better than the non-nickel sample. The samples were added Nickel, the hardness is higher than those without Nickel (105HRB and 92HRB). The abrasion results show that the Nickel alloyed samples also exhibited better than those without Nickel.